IMPLEMENTASI KEBIJAKAN DANA BANTUAN OPERASIONAL SEKOLAH PADA MADRASAH ALIYAH ALKHAIRAAT PUSAT PALU - Wahyu Aldat; Suasa Suasa; Asrifai Asrifai (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine and analyze the implementation of the School Operational Assistance Fund (BOS) Program at Madrasah Aliyah Alkhairaat Central Palu. The research method used was qualitative, and the research informants were determined proportionally who were deemed to understand the problems being studied. The informants were the Head of the Section for Islamic Religious Education, Head of the Palu Central Aliyah Alkhairaat Madrasah, Madrasah BOS Treasurer, Madrasah Committee, Students and Parents. / Guardians of Students. The types of data used are primary data and secondary data. Data collection was carried out by means of observation, interviews and documentation. The results of the research show that the implementation of the Operational Assistance Fund Policy at Madrasah Aliyah Alkhairaat Central Palu has not gone well. Because based on George C Edward III's theory used in this research which consists of (4) Four Aspects, there are still two aspects that are not working optimally. The aspect that has been running optimally is the disposition aspect which is sufficient to support the Implementation of the School Operational Assistance Fund Policy at Madrasah Aliyah Alkhairaat Central Palu, the second aspect which is considered successful is the Bureaucratic Structure aspect which has been running well where all implementors have worked according to their duties and their respective functions. Meanwhile, the communication aspect is one of the main aspects in implementing this policy, communication is the main route for implementing each program. Research results show a lack of communication in the form of socialization carried out by implementors, thus hampering the implementation of the school operational assistance fund policy at Madrasah Aliyah Alkhairaat Central Palu. Meanwhile, from the aspect of human resources, the Madrasah BOS Management is less skilled, resulting in technical obstacles such as the delay in Madrasah BOS Accountability Reports, so this is the influence on the success of the Implementation of the School Operational Assistance Fund Policy at the Palu Central Aiyah Alkhairaat Madrasah.